2020
DOI: 10.29392/001c.12136
|View full text |Cite
|
Sign up to set email alerts
|

Dalits and mental health: investigating perceptions, stigma and barriers to support in Kathmandu, Nepal

Abstract: Back Background ground In Nepal, caste-based disparities have been identified in mental health. The lowest caste, the Dalits, face the greatest discrimination and have a greater prevalence of depression and anxiety when compared with high castes. Therefore, it is important to understand the Dalit communities' perceptions of mental health, the barriers faced when accessing support and to identify the causes of stigma. Investigating this should provide insight to help inform anti-stigma policies and develop inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We found that rural healthcare providers had a high level of awareness and understanding of the cultural, educational and socioeconomic factors behind inequalities in healthcare usage. The lack of awareness, knowledge and education among Dalits and other low castes, their preference for traditional healers, deep-rooted and internalised stigma, and differential parental attitudes towards male and female children, were all commonly identified, and were in accordance with findings in the existing literature from Nepal6 7 10 11 13 25 26 and elsewhere in South Asia 8–10 12 15 16 27 28…”
Section: Discussionsupporting
confidence: 82%
“…We found that rural healthcare providers had a high level of awareness and understanding of the cultural, educational and socioeconomic factors behind inequalities in healthcare usage. The lack of awareness, knowledge and education among Dalits and other low castes, their preference for traditional healers, deep-rooted and internalised stigma, and differential parental attitudes towards male and female children, were all commonly identified, and were in accordance with findings in the existing literature from Nepal6 7 10 11 13 25 26 and elsewhere in South Asia 8–10 12 15 16 27 28…”
Section: Discussionsupporting
confidence: 82%
“…Studies on caste‐based exclusion and mental health report anxiety and depression (French, 2020); social isolation, low self‐esteem, low self‐confidence, withdrawal, and anger (Pal, 2015); and confused self‐identity, hypertension, and neuroticism (Ramaiah, 2007) among respondents. Psychosocial and emotional responses to social exclusion include feelings of disempowerment (Barnes, 1999), trauma (Barnes, 2004; Krishnan, 2015), poor psychological well‐being and self‐harm as a coping strategy (Cleary et al, 2014; Friedli & WHO, 2009; Smith, 2013).…”
Section: Marginalization and Mental Healthmentioning
confidence: 99%
“…Not only in Indian society, but caste also shows its presence in other South Asian countries (Thapa et al, 2021), making the caste system a global issue. Researchers have also revealed the prominence of caste discrimination in the UK (Dhanda, 2017;Gorringe et al, 2017), Kuwait and the UAE (Leonard, 2005). Studies have revealed that caste discrimination is a major issue in the USA and the Dalit diaspora in the US faces severe workplace discrimination (Dutt, 2020;Zwick-Maitreyi et al, 2017).…”
Section: The Caste Systemmentioning
confidence: 99%
“…In terms of life satisfaction, the castes at the top are more satisfied than the lower and middle castes (Fontaine & Yamada, 2014;Landeghem & Vandeplas, 2018;Spears, 2016). In Nepal, a country that follows a caste system similar to India, youth from low caste groups reported more anxiety, depression, and low selfesteem than their counterparts from other caste groups (French, 2020;Kiang et al, 2020).…”
Section: Caste Gender and Well-beingmentioning
confidence: 99%